"SMART WATER" Is an Innovative Method of Water Measurement and Control (Texas Journal of Engineering and Technology, 2023)
Finding a solution to the problems that have arisen and are arising due to the flow of natural resources is a major issue of today. The ecological landscape of the planet Earth was changing in an unprecedented way. Water, which has become a global problem in recent years, has been observed in the countries of the world for many years. This requires saving water and using it efficiently. Reasonable use is not sufficient for this requirement alone. As the problem is global, innovative solutions are needed.